Model Building and Energy Efficient Control of a Series-Parallel Plug-in Hybrid Electric Vehicle - Cid Fernandez, David (My University, 2016)
Among others, one of the European Union 2020 targets is to reduce the overall greenhouse gas emissions by at least 20% compared to 1990 levels. The ongoing introduction of electric and hybrid electric vehicles in the market seems to strongly support this objective. Hybrid electric vehicles (HEV) are those that combine an internal combustion engine with one or more electric machines. Series, parallel and series-parallel are the main HEV topologies. Plug-in hybrid electric vehicles are another topology which allows the battery to be charged using electricity from the grid. Since hybrid electric vehicles combine two or more energy sources, its control becomes really important but challenging at the same time. The role of the energy management strategy is to coordinate the power flow from the mechanical and electrical path. There are mainly two general energy management strategies: rule-based strategies and optimization-based algorithms. In this thesis, a model of a series-parallel plug-in hybrid electric vehicle is built using Matlab Simulink and its toolbox QSS. A gearbox controller that selects the best gear each timestep is also included in order to control the automatic gearbox that connects the ICE with the front shaft. Furthermore, two different energy management strategies are implemented and compared mainly in terms of fuel consumption and battery SOC profile for various driving cycle conditions and different battery discharging modes. A rule-based strategy is compared with the Equivalent Consumption Minimization Strategy (ECMS) which is based on optimization algorithms. The results show that the ECMS strategy reduces the fuel consumption in the range of 8-20 % depending on the driving cycle and battery discharge strategy compared to the rule-based strategy. Moreover, a PHEV model without generator is also modeled in order to analyze the influence of the generator on fuel consumption. The fuel consumption significantly increases due to the generator removal in all studied cases and the battery SOC profiles show higher variations from its reference value. Finally, some future work suggestion are pointed out in order to guide further researches in this topic.
Keywords: Elkraftteknik; Electric power engineering